2017
DOI: 10.1039/c7cy00154a
|View full text |Cite
|
Sign up to set email alerts
|

Highly active and stable interface derived from Pt supported on Ni/Fe layered double oxides for HCHO oxidation

Abstract: In this work, Ni/Fe layered double oxide supported Pt nanoparticles (Pt/LDO(N)) were prepared using a hydrothermal and colloid-impregnation method. The catalyst exhibited remarkable HCHO oxidation ability and long-time stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…Generally, the supported noble metal catalysts exhibit higher catalytic activities in HCHO oxidation at room temperature than metal oxide catalysts. And the supported Pt catalyst is the most active catalyst for HCHO oxidation at room temperature and attracts much attention . However, the high cost and limited resources hinder the application of supported noble metal catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the supported noble metal catalysts exhibit higher catalytic activities in HCHO oxidation at room temperature than metal oxide catalysts. And the supported Pt catalyst is the most active catalyst for HCHO oxidation at room temperature and attracts much attention . However, the high cost and limited resources hinder the application of supported noble metal catalysts .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9] Generally, noble metal oxide catalysts exhibit high catalytic activity at low temperatures for deep oxidation of VOCs. [10][11][12][13][14][15] However, their practical applications are greatly limited due to their high cost, easy sintering and poisoning nature. Compared with precious metal oxides, various active transition metal oxides (Co 3 O 4 , Mn 3 O 4 , CeO 2 , Fe 2 O 3 , NiO, TiO 2 , etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Generally, noble metal oxide catalysts exhibit high catalytic activity at low temperatures for deep oxidation of VOCs . However, their practical applications are greatly limited due to their high cost, easy sintering and poisoning nature.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the ratio of Ga + /Ga 3 + increased with a rise in calcination temperature. For each sample, the O 1s spectrum ( Figure 6C) could be decomposed to three components at BE = 530.8, 531.9, and 533.4 eV, attributable to the surface lattice oxygen (O latt ), adsorbed oxygen (O ads ), and adsorbed molecular water, [25,26] respectively. Compared the O 1s XPS spectra of pure support Pd/Al 2 O 3 and PdÀ GaO x /Al 2 O 3 ( Figure S11 and Figure 6C), we found that the binding energy of O in Pd/Al 2 O 3 and pure support is similar while the binding energy of O in PdÀ GaO x /Al 2 O 3 shift to the higher energy.…”
Section: Resultsmentioning
confidence: 99%